2018
DOI: 10.22159/ijap.2018.v10s1.22
|View full text |Cite
|
Sign up to set email alerts
|

Cyclea Barbata Leaf Extract: Lipoxygenase Inhibitory Activity and Phytochemical Screening

Abstract: Objective: The aim of this study was to test the anti-inflammatory activity of methanol, ethyl acetate, and n-hexane Cyclea barbata Miers. leaf extracts using a lipoxygenase inhibition method.Methods: Enzyme activity assay was performed using colorimetric method with lipoxygenase from soybean and linoleic acid as a substrate. Absorbance was measured at 234 nm. The total flavonoid content of the most active extract was determined using a colorimetric method with AlCl 3 and phytochemical screening. Results:The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…It was reported that flavonoids have many benefits, such as antibacterial, anti-inflammatory, anticancer, antioxidant, hepatoprotective, and antiviral properties [ 55 , 56 ]. Handayani et al reported inhibition of LOX with leaf extracts of C. Barbarata [ 57 ]. Three various solvents (ethyl acetate, n -hexane, and methanol) were employed for extraction.…”
Section: Lipoxygenase Inhibition By Plant Extracts Of Family Menismentioning
confidence: 99%
“…It was reported that flavonoids have many benefits, such as antibacterial, anti-inflammatory, anticancer, antioxidant, hepatoprotective, and antiviral properties [ 55 , 56 ]. Handayani et al reported inhibition of LOX with leaf extracts of C. Barbarata [ 57 ]. Three various solvents (ethyl acetate, n -hexane, and methanol) were employed for extraction.…”
Section: Lipoxygenase Inhibition By Plant Extracts Of Family Menismentioning
confidence: 99%
“…Berdasarkan hasil tersebut dapat dilihat bahwa efek antiinflamasi ekstrak etanol daun C. barbata dosis 7,5 mg/kgBB hampir setara dengan kontrol positif Na.Diklofenak yakni sebesar 38.43%. Penelitian lainnya dilakukan oleh Handayani et al, (2018) untuk menghambat aktivitas lipoxygenase. Persentase nilai penghambatan tertinggi ekstrak etil asetat sebesar 53.76%, sehingga diperoleh nilai IC50 0.267 µg/mL.…”
Section: Antiinflamasiunclassified
“…The flavonoids have the potential to inhibit the expression of isoforms that induce nitric oxide, cyclooxygenase, and lipoxygenase, which manage the production of nitrate oxide, prostanoids, leukotrienes, and any other mediators of the inflammatory process, like cytokines and chemokines. Thus, the flavonoid compounds in Cyclea barbata leaves are thought to inhibit the formation of leukotriene, and also have an anti-inflammatory effect [10]. Handayani N.F., et al, research shows that the ethyl acetate extract from Cyclea barbata leaves the highest lipoxygenase inhibitory activity, with an IC50 of 0.267 mg/mL.…”
Section: Introductionmentioning
confidence: 99%